Gd-EOB-DTPA-Enhanced Magnetic Resonance Imaging for Assessing Liver Function in Primary Biliary Cholangitis - Li, Zhengjun; Zhang, Fan; Lu, Weiting; Lu, Chao; Yuan, Zheng; Wang, Zhongqiu (Current Medical Imaging, 2025)
IntroductionThis study aimed to detect the performance of gadolinium ethoxybenzyl diethylenetriamine pentaacetic acid (Gd-EOB-DTPA)-enhanced magnetic resonance imaging (MRI) for assessing primary biliary cholangitis (PBC).MethodsSeventy-five patients with PBC were included in this prospective study. Shear wave elastography (SWE) and Gd-EOB-DTPA-enhanced MRI were conducted, and then the signal intensity ratio (SIR) and contrast enhancement index (CEI) in different phases, including portal venous phase (PVP), equilibrium phase (EP), and hepatobiliary phase (HBP), were calculated. Afterward, the results were compared with Child-Pugh grading and non-invasive liver fibrosis models using the Kruskal-Wallis H test or Chi-squared test. The area under the curve (AUC) was applied to evaluate the diagnostic performance of SIRHBP, CEIHBP, and SWE across different Child-Pugh grades.ResultsSWE (p0.001), SIR HBP (p0.001), CEIHBP (p0.001), APRI (p=0.002), and FIB-4(p0.001) showed significant differences in different Child-Pugh grades. Statistically significant differences were found in SIRHBP (p=0.005), CEIHBP (p=0.010), and FIB-4 (p=0.001) of different SWE levels. For the diagnosis of Child-Pugh C, the AUC of SWE, SIRHBP, and CEIHBP were 0.889, 0.778, and 0.761, respectively. Correspondingly, the sensitivity was 75.0%, 64.4%, and 54.2%, and the specificity was 94.9%, 100%, and 100%, respectively. For the diagnosis of Child-Pugh B+C, the AUC of SWE, SIRHBP, and CEIHBP were 0.919, 0.809, and 0.814, respectively.DiscussionOur study confirmed that Gd-EOB-DTPA-enhanced MRI is an effective and objective method for assessing liver function in patients with PBC.ConclusionSIRHBP and CEIHBP could be regarded as a novel imaging biomarker to evaluate liver function. Gd-EOB-DTPA-enhanced MRI and SWE outperformed serum-based models in sensitivity and specificity, strengthening the value of imaging in clinical decision-making.
Keywords: Primary biliary cholangitis